An enhanced ascorbate peroxidase 2/antibody-binding domain fusion protein (APEX2–ABD) as a recombinant target-specific signal amplifier1. Issue 54 (11th July 2015) - Lee, Jisu; Song, Eun Kyung; Bae, Yoonji; Min, Junseon; Rhee, Hyun-Woo; Park, Tae Joo; Kim, Moonil; Kang, Sebyung
<x xml:space="preserve">Abstract</x> A recombinant target-specific signal amplifier was constructed and used in a TSA assay for amplifying signals.